Collect Earth: An online tool for systematic reference data collection in land cover and use applications. (August 2019) - Saah, David; Johnson, Gary; Ashmall, Billy; Tondapu, Githika; Tenneson, Karis; Patterson, Matt; Poortinga, Ate; Markert, Kel; Quyen, Nguyen Hanh; San Aung, Khun; Schlichting, Lena; Matin, Mir; et al.
Abstract: Land cover monitoring efforts are important for resource planning and ecosystem services in many countries. Collect Earth Online (CEO) is a new, free open source and user-friendly software tool for land monitoring. It is the product of a collaborative effort between NASA, Food and Agriculture Organization of the United Nations (FAO), US Forest Service and Google. This paper provides a full overview of CEO's structure and functionality. Based on the cloud, CEO's structure supports simultaneous data entry by multiple users. No desktop installation is required and only an internet connection is required setting minimal requirements for using the software. Google Earth Engine widgets can be created for assisted plot interpretation such as image collection, time series graphs featuring indices such as Normalized Difference Vegetation Index (NDVI) and related statistics. We also provide a case study and related findings from a CEO workshop held in Myanmar. Highlights: Collect Earth Online (CEO) is a new, free, open source tool for land monitoring. It is built on joint efforts between NASA, FAO, US Forest Service and Google. CEO is free and meets key reference data collection requirements for practitioners. It is a robust, integrated approach for data collection in collaborative settings. A case study using CEO for reference data collection in Myanmar is presented.